2016
DOI: 10.5194/soil-2-63-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use changes on the dynamics of selected soil properties in northeast Wellega, Ethiopia

Abstract: Abstract. Land use change can have negative or positive effects on soil quality. Our objective was to assess the effects of land uses changes on the dynamics of selected soil physical and chemical properties. Soil samples were collected from three adjacent soil plots under different land uses, namely forestland, grazing land, and cultivated land at 0–15 cm depth. Changes in soil properties on cultivated and grazing land were computed and compared to forestland, and ANOVA (analysis of variance) was used to test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 35 publications
7
44
0
4
Order By: Relevance
“…When the areas were compared in terms of content of P, it was found that mined area had less amount of P than the other areas since the mined areas hadn't been farmed for a long time. These results exhibited similarity with the parameters in which P values increased by the use of farming activities as reported by Adugna and Abegaz (2016). Content of K and Mg of soil samples were high and calcium was in medium/good level.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…When the areas were compared in terms of content of P, it was found that mined area had less amount of P than the other areas since the mined areas hadn't been farmed for a long time. These results exhibited similarity with the parameters in which P values increased by the use of farming activities as reported by Adugna and Abegaz (2016). Content of K and Mg of soil samples were high and calcium was in medium/good level.…”
Section: Resultssupporting
confidence: 87%
“…Most of the samples had no salinity problem, alkali-reaction, limy and soil which was poor in terms of organic substance and nitrogen. The content of clay, sand, pH and organic matter of soil change with type of land usage and that the amount of silt increase due to agricultural practices (Adugna and Abegaz, 2016). Similarly, pH value of soil tend to decrease (Abad, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Adugna ve Abegaz [30] ile Sarıyıldız ve ark. [23] benzer şekilde kum miktarının tarım alanlarında orman ve meraya göre daha yüksek olduğunu saptamışlardır.…”
Section: Dispersiyon Oranıunclassified
“…The contribution of root inputs to organic C can greatly influence both the total amount and vertical distribution of SOC in different depth of soil (Oelbermann and Voroney, 2007;Rumpel and Kogel-Knabner, 2011).Similar findings were reported by Keen et al (2011). Conversion to oil palm plantation led to a net gain of soil C stock (Flynn et al, 2012;Frazao et al, 2013;Patthanaissaranukool and Polprasert, 2011;Siangjaeo et al, 2011) due to suitable land management systems (Adugna and Abegaz, 2016;Six et al 2002). Land use change can lead to an alteration of the amounts and qualities of SOM (Coleman et al, 1989) and can potentially either release or sequester soil carbon (Mendham et al, 2003).…”
Section: Soil Organic Mattermentioning
confidence: 99%